2020
DOI: 10.3390/ijerph17176182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Consequences of SARS-CoV-2 Pandemic on a Single University Dermatology Outpatient Clinic in Germany

Abstract: The pandemic outbreak of coronavirus disease 2019 (COVID-19) affects health care systems globally and leads to other challenges besides infection and its direct medical consequences. The aim of this study was to investigate the impact of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) pandemic on the university dermatology outpatient clinic (UDOC) of the Technical University of Munich, Germany. We analyzed datasets from 2015 until 2020 extracted from the hospital information system database and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 22 publications
4
37
0
22
Order By: Relevance
“…1 ). Dies führten die Autoren darauf zurück, dass zur Pandemiezeit weniger Menschen dermatologische Leistungen in Anspruch genommen haben [ 35 ].
…”
Section: Zeitliche Trends Und Zusammenhang Mit Externen Faktorenunclassified
“…1 ). Dies führten die Autoren darauf zurück, dass zur Pandemiezeit weniger Menschen dermatologische Leistungen in Anspruch genommen haben [ 35 ].
…”
Section: Zeitliche Trends Und Zusammenhang Mit Externen Faktorenunclassified
“…Multiple barriers to care delivery were noted during this time [ 166 ]. For instance, one study reported that older adults were more likely to miss or cancel medical appointments [ 129 ], whereas another reported the opposite [ 60 ]. One study reported that treatment delays and postponed appointments were more common among older adults [ 130 ], whereas another reported this was more commonly observed among younger people [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Die Auswirkungen dieser über viele Monate andauernden Mangelverwaltung sind in ihrem Ausmaß noch nicht abschließend einzuschätzen. Auffällig war auch, dass viele Patient:innen – offenbar aus Angst vor Ansteckung oder Unsicherheit wegen der allgemeinen politischen Ratlosigkeit im Umgang mit der Corona‐Pandemie – die Krankenhäuser mieden, selbst wenn sie behandlungsbedürftige schwere Hautkrankheiten oder Hauttumoren hatten [1]. Die DDG hat zusammen mit dem BVDD Empfehlungen zum Management von Patienten mit chronischen Hautkrankheiten unter Pandemie‐Bedingungen veröffentlicht, die auch den Umgang mit neu einzuleitenden oder laufenden Systemtherapien beinhalteten [2–4].…”
Section: Abbildungunclassified